Peningkatan Hasil Belajar IPS Menggunakan Model Cooperative Learning Tipe Numbered Heads Together di Kelas V SD - utami, siska putri; abidin, zainal; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the social studies learning used NHT of 5th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 5th grade were 25 people of 10 men and 15 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 80% and the cycles II of 96,42% b) Implementation teacher’s activity of I cycle was 81,25% and II cycle was 96,8% while implementation students activity of I cycle was 78,12% and II cycle was 96,8% c) the students learning outcomes in the I cycle was 77,1 and II cycle was 87,3. It can be concluded that used NHT model can improve students achievement in learning social science of 5th grade at SDN 18 Air Tawar Padang.Keyword : Learning outcomes, Social science, NHT